2021
DOI: 10.1155/2021/9915877
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Shockwave Therapy Modulates the Expressions of Proinflammatory Cytokines IL33 and IL17A, and Their Receptors ST2 and IL17RA, within the Articular Cartilage in Early Avascular Necrosis of the Femoral Head in a Rat Model

Abstract: Avascular necrosis (AVN) of the femoral head (AVNFH) is a disease caused by injury to the blood supply of the femoral head, resulting in a collapse with osteonecrosis and damage to the articular cartilage. Extracorporeal shockwave therapy (ESWT) has been demonstrated to improve AVNFH owing to its anti-inflammation activity, angiogenesis effect, and tissue regeneration in clinical treatment. However, there are still so many pieces of the jigsaw that need to be fit into place in order to ascertain the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 46 publications
0
16
1
1
Order By: Relevance
“…Similar to our study, a significantly lower level of IL-1β had been observed in the ESWT group than in the sham-ESWT group in avascular necrosis of the femoral head in rats. 5 However, the changes in IL-1β concentrations after ESWT were not consistent in the current animal studies. According to Chen et al, 4 the IL-1β concentration remained stable over time during the post-ESWT period.…”
Section: Discussioncontrasting
confidence: 61%
“…Similar to our study, a significantly lower level of IL-1β had been observed in the ESWT group than in the sham-ESWT group in avascular necrosis of the femoral head in rats. 5 However, the changes in IL-1β concentrations after ESWT were not consistent in the current animal studies. According to Chen et al, 4 the IL-1β concentration remained stable over time during the post-ESWT period.…”
Section: Discussioncontrasting
confidence: 61%
“…Inflammatory factors are associated with KOA disease progression. Multiple studies have identified the effects of ESWT on the reduction of inflammation in animal models [ 83 , 84 ] and human osteoarthritic chondrocytes [ 85 , 86 ]. Analysis results in the present NMA revealed that high-EFD FoSW exerted significant effects on disease inflammation in terms of decrease in joint inflammation and was ranked the most optimal option among ESWT treatment arms.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 LiESWT treatment has anti-inflammatory effects through modulation of anti-inflammation markers such as sICAM, sVCAM, and pro-inflammatory cytokines IL33 and IL17A. 20,21 Decrease of neurons immunoreactive for substance P results in long-term analgesia with LiESWT application to the musculoskeletal system. 22 As a result, the anti-inflammatory effect may be the main mechanisms to resolve the pain and other symptoms in IC/PBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cell activation and neurogenic inflammation may cause neuro‐sensitization, which may be related to the level of substance P, and lead the chronic pain 18,19 . LiESWT treatment has anti‐inflammatory effects through modulation of anti‐inflammation markers such as sICAM, sVCAM, and pro‐inflammatory cytokines IL33 and IL17A 20,21 . Decrease of neurons immunoreactive for substance P results in long‐term analgesia with LiESWT application to the musculoskeletal system 22 .…”
Section: Discussionmentioning
confidence: 99%